AN ANIMATED MODELS DEVELOPMENT OF CARDIOVASCULAR SYSTEM IN PHARMACOLOGY LEARNING MODULE FOR MEDICAL STUDENTS - Bernadette Dian Novita; Paul L Tahalele; Gerardo AK Laksono (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Hypertension is the most known common cardiovascular disease. Based on the Indonesian Competency Standard of Medical Doctors (StandarKompetensiDokter Indonesia or SKDI), the management of essential hypertension is at 4A or the highest level. Therefore, doctors should be able to establish a complete and independent diagnosis and management. The student passing rate in the cardiovascular system at the undergraduate level of medical education of Faculty of Medicine Widya Mandala Catholic University (FK UKWMS) was around 60-70%. This study is an evaluation to develop learning methods that would improve student learning outcomes. The development of this animation model is aimed to increase the engagement process in Pharmacology learning, especially in the cardiovascular system. 98 active students participated in this study, divided into 74 undergraduate students and 24 clinical internship students. The evaluation was carried out using a pre-test and a post-test related to pharmacological animation video exposure. Using the Wilcoxon different test, there was a significant difference between the pre-test and post-test results, especially in the clinical internship program’s students. This animated model was expected to help students to determine the rational determination of hypertension therapy.